Relationship Of Physical Activity To Total Fat Mass Of Lecturers And Employees Bengkulu University - Syafrial Syafrial; Tono Sugihartono; Yarmani Yarmani; Arwin Arwin; Ari Sutisyana; Riskia Eka Putri; Novriansyah Novriansyah; Defliyanto Defliyanto (UNIB Press, 2020)
Insufficient physical activity and accumulation of body fat mass are risk factors for chronic disease. Physical activity is needed to prevent the risk of chronic disease due to body fat accumulation. This research is an observational analytic study with a cross sectional design. A sample of 52 people was taken by consecutive sampling method including lecturers and employees aged 30-60 years at the Faculty of Teacher Training and Education, University of Bengkulu (FKIP UNIB). Physical activity was analyzed using the Physical Activity Level (PAL) questionnaire, total fat mass was assessed by means of Bioelectrical Impedance Analysis (BIA). Data distribution analysis was tested using the Kolmogorov-Smirnov test. Analysis of the relationship between two categorical variables with the Chi-square test, the Kruskal-Wallis and Mann Whitney test. The correlation analysis between the two variables was analyzed using the Gamma correlation test. The results of this study indicate that there is a significant relationship between physical activity and total fat mass (p = 0.031, r = 0.428) after being analyzed with Gamma correlation. It can be concluded that physical activity has a relationship with total fat mass.